UNDERSTANDING KAMPUNG MADRAS OF INDONESIA LIMITED PROMINENCE VERSUS MALAYSIA AND SINGAPORE LITTLE INDIAS - Lebin, Havilah Labora; Ginting, S. W. (GoAcademica Research dan Publishing, 2026)
As debates on multicultural heritage intensify across Southeast Asia, this study investigates the architectural and cultural conditions that shape the identity of Kampung Madras in Medan in comparison with Little India districts in Penang, Kuala Lumpur, and Singapore. While these three enclaves have undergone coordinated conservation efforts, curated streetscape enhancement, and cultural programming that reinforce their Indian heritage, Kampung Madras presents a contrasting trajectory. Its temples, shophouses, and commercial corridors reflect traces of Indian architectural tradition, yet appear fragmented due to unregulated growth, weak façade continuity, and limited municipal intervention. Intangible cultural life in Kampung Madras remains vibrant through rituals, festivals, and intergenerational practices, but these expressions operate with minimal public visibility and rely almost entirely on community initiative. In the comparative cases, similar traditions are supported, staged, and woven into city branding, enabling a stronger symbolic presence. Through qualitative analysis supported by visual documentation, this study shows that the reduced prominence of Kampung Madras is rooted in policy gaps, uneven heritage governance, and the absence of culturally sensitive planning mechanisms that have long guided the development of Penang, Kuala Lumpur, and Singapore’s Little Indias. The study argues that recognizing enclaves like Kampung Madras as integral components of urban multicultural identity is essential for sustaining their architectural and cultural vitality. It suggests that heritage-sensitive zoning, inclusive conservation strategies, and participatory planning are necessary to strengthen Medan’s commitment to cultural diversity and enhance the resilience of its Indian enclave.